Development of the Advertising Specialty in Higher Education in Russia and China - Yuzhi Wang; Elena N. Remchukova (Peoples' Friendship University of Russia (RUDN University), 2021)
The process of globalization and the emergence of various new media are currently increasing the importance of the study of advertising in various fields, including higher education. This is due to the fact that the ability of manufacturers to create and display advertising texts makes it possible to effectively promote ideas, goods or services around the world for commercial and non-commercial purposes. The research is devoted to a comparative analysis of the development of the advertising specialty in higher education in post-Soviet Russia (1991-2020) and in the Peoples Republic of China (1949-2020). It presents the history of the formation and development of the advertising specialty in Russian and Chinese universities. The authors investigate the extent to which the development of this specialty in universities complies with the requests of government agencies and of the advertising industry in Russia and China in different periods. The goal of the study is to examine the specifics of the development processes of the advertising specialty in Russia and China and to identify their advantages and disadvantages. Addressing the topic is relevant due to the intensity of the development of advertising and to the need to search for new forms of learning for the further development of this promising specialty in higher education. The results of the analysis have helped identify similarities and differences in the development of these processes in the two countries and describe specific features of the latter with due account of social, economic and historical factors at various stages of development. The obtained data proves that, along with similarities, the development of the advertising specialty in higher education in Russia and China has certain differences, which is directly related to the ideological atmosphere, financial state, economic strategies, and higher education standards in the two countries.